Genomic and functional analysis of isochorismate synthase genes in sugarcane and their roles in disease resistance - Zhen Zeng; Xinyu Zhu; Jiaoyun Chen; Shilong Zhang; Sisi Zhou; Kailin Li; Wankuan Shen (Crop Journal)
Isochorismate synthase (ICS), a key rate-limiting enzyme in the salicylic acid (SA) biosynthesis pathway in plants, is essential for plant growth and defense against diseases. However, there has been no report on ICS in sugarcane (Saccharum spp.). In this study, 18 SsICSs, 42 ShICSs, and 36 SzICSs were identified from the genomes of sugarcane AP85-441 (Saccharum spontaneum), XTT22 (Saccharum spp. hybrid cultivar), and ZZ1 (Saccharum spp. hybrid cultivar), respectively. These were phylogenetically divided into three groups, forming distinct clades that were evolutionarily divergent from those in dicotyledonous species. The evolutionary profile of the ICS gene family suggested expansion through whole-genome duplication/segmental events and strong purifying selection. Promoter cis-element and transcriptome analyses indicated that the ICS gene family responded to disease stress. We cloned the ScICS (isochorismate synthase) gene from sugarcane cultivar XTT22 leaves, and found it was localized in chloroplasts. In vivo and in vitro interaction studies revealed an interaction between ScICS and an ScMYB transcription factor. We showed that ScWRKY28 positively regulated ScICS expression by binding to its promoter. ScICS overexpression in transgenic tobacco confirmed its effectiveness in enhancing disease resistance. There was a significant increase in SA content following pathogen infection along with activation of downstream signaling pathways and defense mechanisms. This study establishes the groundwork for functional studies of sugarcane ICS genes and enhances our understanding of the mechanisms of disease resistance in sugarcane.